СLINICAL-EPIDEMIOLOGICAL, IMMUNOLOGICAL, MICROBIOLOGICAL ASPECTS AND PREVALENCE OF BLASTOCYSTOSIS AMONG THE POPULATION OF THE REPUBLIC OF AZERBAIJAN - Mammadova, N.O. (World of Medicine and Biology, 2024)
Blastocystosis is one of the least studied infectious diseases among intestinal protozoans in the Republic of Azerbaijan; only several studies have been conducted in this field, dating back 30–35 years. The attitude towards blastocystosis worldwide, including in the Republic of Azerbaijan, has not been unambiguous. We have discovered epidemiological features and regional characteristics. As a result, three subtypes of Blastocystis hominis have been identified – ST3, ST2, and ST4. For example, ST3 was found the most, followed by ST2, and relatively less ST4. Therefore, it is essential to study the prevalence of B.hominis among populations in different regions and countries and to study the role in human pathologies, its pathogenesis, and clinical course caused by different species and genotypes, which lead to the effectiveness of treatment.
Keywords: blastocystosis; genotypes; morbidity; opportunistic infection; cytokines; intestinal microbiota; conditionally pathogenic microflora; diarrhea